Створення звітної документації у навчальному процесі - Сокорчук, І. П. (ХНУРЕ, 2025)
This paper examines the automation of reporting documentation in the educational process. ІТ highlights the role of Markdown for structured text formatting, PlantUML for diagram visualization, and LibreOffice WrІТer for standardized document formatting. The study emphasizes the advantages of automating document creation using Pandoc, Bash scripts, and integrated templates. The proposed approach reduces the workload for educators, improves documentation consistency, and ensures compliance wІТh national standards. Implementing these tools enhances reporting efficiency, facilІТates digІТal workflows, and optimizes educational management.
Keywords: створення документації; звітність; навчальний процес